Application of probiotics, prebiotics and synbiotics in patients with breast cancer: a systematic review and meta-analysis protocol for randomised controlled trials. Issue 11 (10th November 2022) - Duan, Dan; Chen, Maojun; Cui, Wenyao; Liu, Wenjie; Chen, Xinrong
Abstract : Introduction: Breast cancer has become a common tumour that threatens women's physical and mental health. Microbial agents play an important role in maintaining the balance of gut microbiota and modulating intestinal immunity, anti-inflammatory and antioxidant effects. Available evidence points to a strong association between them and breast cancer. However, there has been no systematic review of the effects of microbial agents in patients with breast cancer. This protocol aims to explore the effectiveness and safety of probiotics, prebiotics and synbiotics in patients with breast cancer. Methods and analysis: We will search the following electronic databases for relevant randomised controlled trials: PubMed, EMBASE, Cochrane Library and Web of Science. Grey literature and reference lists of original studies will also be searched to avoid omissions. We will use the Cochrane Collaboration's Risk of Bias tool to assess the quality of the included studies. The primary outcomes include patients' arm oedema volume, changes in gut microbiota composition and anthropometric parameters. Two independent reviewers will perform literature screening, data extraction and risk of bias assessment. Data synthesis will be performed using descriptive analysis or meta-analysis. The quality of the evidence for each outcome will be assessed using the Grading of Recommendations Assessment, Development and Evaluation tool. Ethics and dissemination: The data for systematic reviews are derived from published original studies and do not require review and approval by the ethics committee. The results will be disseminated through a peer-reviewed journal and conferences. PROSPERO registration number: CRD42022311502.